Democratising Participatory Research : Pathways to Social Justice from the South. - Martinez-Vargas, Carmen. (Open Book Publishers, 2022)
In this book Carmen Martinez-Vargas explores how academic participatory research and the way it is carried out can contribute to more, or less, social justice. Adopting theoretical and empirical approaches, and addressing multiple complex, intersectional issues, this book offers inspiration for scholars and practitioners to open up alternative pathways to social justice, viewed through a Global South lens.